1987
DOI: 10.1002/jobm.3620270907
|View full text |Cite
|
Sign up to set email alerts
|

Selektion und biotechnische Herstellung von Kulturlösungen mikrobieller Antagonisten zur Unterdrückung phytopathogener Bodenpilze

Abstract: Two strains of bacteria, Bacillus subtilis T 99 and Streptomyces sp. G 43, antagonistic t o phytopathogenic soil fungi, were isolated from natural substrates. In vitro tests indicated activities against different Fusarium species including formae speciales of Fusarium oxysporum, Stromatinia gladioli, Botrytis cinerea, Thanatephorus cucumeris, and other fungi. For both of the antagonists, biotechnical procedures were developed yielding culture broth for large-scale application. After dilution of these media ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…1989 ). However, it has often been reported as an antifungal agent against plant pathogens ( Huber et al . 1987 ; Hebbar et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1989 ). However, it has often been reported as an antifungal agent against plant pathogens ( Huber et al . 1987 ; Hebbar et al .…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus subtilis is not a typical rhizobacterium; it also occurs in the soil surrounding the root (Miller et al 1989). However, it has often been reported as an antifungal agent against plant pathogens (Huber et al 1987;Hebbar et al 1991;Milus and Rothrock 1993). Bacillus subtilis A13 was categorized as a plant growth-promoting rhizobacterium (PGPR) by Kloepper et al (1989).…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal activity against F. oxysporum and R. solani of this crude supernatant was determined using the method of Huber 14 . Different amounts of the crude supernatant were added to potato dextrose agar (PDA) at 55°C, mixed well, and poured into Petri dishes (90 × 15 mm).…”
Section: Antifungal Activity Of the Crude Bacterial Supernatant Determentioning
confidence: 99%
“…Antifungal activity of the extracellular extracts The extracellular extracts from Serratia marcescens DT3 were obtained by centrifuging the bacterial culture at 17,460 × g for 10 min. The antifungal activity of this extracellular extract was determined using the method of Huber et al (1987). Different amounts of extracellular extracts were added to potato dextrose agar (PDA) at 55 °C, mixed well, and poured into petri dishes (90 × 15 mm).…”
Section: Protein Identificationmentioning
confidence: 99%
“…Three different concentrations of extracellular extracts (20%, 30%, and 50%) of Serratia marcescens DT3 were tested for their antifungal activity against Rhizoctonia solani and Fusarium oxysporum using the method of Huber et al, (1987). The results (Table 1) showed that the extracellular extracts of Serratia marcescens DT3 have significant antifungal activity on both fungal pathogens.…”
Section: Antifungal Activity Of the Extracellular Extracts Of S Marcescens Dt3mentioning
confidence: 99%